Seropositivity of Dengue in and around Akola, Maharashtra - Seematai Prakash Katole; Sharmila S Raut; Nazneen I Malak; Nitin A Ambhore (Journal of Medical Sciences and Health)
Background: Dengue, also known as "tropical flu," is a viral disease transmitted to humans by Aedes mosquito. Dengue fever is a deadly arboviral disease caused by any of the five serotypes DENV1, DENV2, DENV3, DENV4 and DENV5 which are placed in the Family Flaviviridae and genus Flavivirus. Each serotype of the virus produces a specific, lifelong immunity, but it provides only a short term cross-immunity. Aim and Objective: To determine the seropositivity of Dengue in suspected cases in and around Akola, Maharashtra. Materials and Methods: This study was done on the samples received for dengue testing at Department of Microbiology, Government Medical College Akola Maharashtra. Study was carried out from January 2015 to April 2024. Blood samples were collected from 13,554 patients with dengue like clinical illness and serum was separated. All the samples were subjected to IgM antibody detection by dengue MAC ELISA. Results: Seropositivity of dengue in dengue suspected cases was found to be15.43% (2092/13554). Maximum number of positive cases, 628(30.00%) were in the age group of 11-20 years. Males 1209(57.80%) were affected more than females 883(42.20%). Peak was observed in the months of November followed by October followed by September followed by August. Common presenting features were fever followed by myalgia, arthralgia, headache, and bleeding manifestations. Conclusion: Surveillance is prerequisite for monitoring the dengue situation in the area and should be carried out regularly for early detection of an impending outbreak